DAMPAK PENGGUNAAN MEDIA SOSIAL DENGAN METODE SYSTEMATIC LITERATURE REVIEW - Elfira, Galluh Yogi; Syaputra, Muhammad Adie (Institut Bakti Nusantara, 2024)
The various effects of social media can impact individuals, society, even institutions and organizations. This research aims to study the effects of using social media on the platforms most frequently used by users, both from positive and negative aspects, through literature analysis using the Systematic Literature Review method by collecting data from relevant journals from 2019 to 2023. Based on the SLR results, researchers found 70 journals in a search using Publish or Perish via Crossref. These journals were then filtered into 43 journals selected for descriptive analysis. The SLR results show that from 2019-2023, Instagram becomes the dominant platform with positive impacts, and structured methods dominate.